Organic matter dynamics in Nylsvley Wetland : Distribution and processes - Makhuvha, Lufuno (My University, 2021)
Wetlands play a crucial role in nutrient and biogeochemical cycles and are among the most productive of ecosystems. Physical and biological processes are involved in the distribution and protection of organic matter in wetlands sediments. Productivity among wetlands therefore varies depending on the type of the wetland, climatic condition and vegetation communities. The application of biogeochemical techniques involving stable isotopes of carbon and nitrogen has been successfully used to determine sediment sources in aquatic ecosystems such as wetlands. The study investigated spatial and temporal changes in sources of organic matter in sediments and examined spatial and seasonal changes over two seasons within Nylsvley wetland. Samples of sediments were collected at each wetland site per season in order to determine amount of organic matter and to identify contributors to sediment organic matter. These samples were air dried and impurities removed, then put into the oven and dried at 60 °C to constant weight for 72 hours. Data was analyzed using a three–way ANOVA with Tukey’s HSD analysis ed to assess the differences in sediment organic matter (%) among wetland zones, sites and seasons. A Stable Isotope Analysis in R (SIAR) model was used to identify organic matter sources contributing to sediments in wetland zones per season. Results showed distribution was uneven throughout the wetlands; the seasonal zone had the highest sediment organic matter (27%) in the cool-dry season and the permanent zone had the highest (25%) sediment organic matter in the hot-wet season and the temporary zone had the lowest. Several studies have indicated that ∂13C and ∂15N can be used as indicators for environmental change. Carbon and Nitrogen stable isotope may be an alternative means to detect early environmental changes in aquatic ecosystems including wetlands. 3 The seasonal zone had a high nutrient concentration (Calcium) in both hot-wet and cool-dry season ranging between 1000-1800 mg kg-1. Autochthonous plants were the main source of organic matter in sediments although allochthonous plants also contributed to the sediment organic matter content, autochthonous inputs was still dominant. In sediments the ∂13C mean values were higher than the ∂15N values in all sites and wetland zones. This study showed that sediment organic matter in wetlands is mainly derived from autochthonous sources. This study’s findings help to better understand the distribution of organic matter in wetland ecosystems. This is particularly important as wetlands play a vital role globally by their contribution to provisioning, regulating and cultural services. As such, future studies should continue to assess seasonal variations and identifying other sources of organic matter within the context of distribution and processes in wetland ecosystems not only in South Africa but globally.
MENVSC
Department of Ecology and Resource Management
Keywords: Wetlands; UCTD; Stable isotopes; Allochthonous and autochthonous; Organic matter; 551.4170968; Wetlands -- South Africa; Land use -- South Africa; Landforms -- South Africa